2008
DOI: 10.1021/jo801539w
|View full text |Cite
|
Sign up to set email alerts
|

Aminolysis of O-Aryl Thionobenzoates: Amine Basicity Combines with Modulation of the Nature of Substituents in the Leaving Group and Thionobenzoate Moiety to Control the Reaction Mechanism

Abstract: A kinetic study is reported for aminolysis of O-Y-substituted phenyl thionobenzoates (1a-f) and O-4-nitrophenyl X-substituted thionobenzoates (2a-f) in 80 mol % H2O/20 mol % DMSO at 25.0 +/- 0.1 degrees C. The reaction proceeds through one or two intermediates (i.e., a zwitterionic tetrahedral intermediate T(+/-) and its deprotonated form T(-)) depending on the basicity difference between the nucleophile and nucleofuge, that is, the reaction proceeds through T(+/-) when the leaving aryloxide is less basic than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Deviations from Hammett plots based on standard σ galues have been rarely reported in S N Ar reactions, but have been commonly observed in the S N 2 process 33,34. Koh and coworkers, for example, investigated the reactions of substituted phenacyl bromides with pyridines in acetonitrile at 45°C and the curved Hammett plots have been interpreted in terms of a change in the rate‐determining step from breakdown to formation of a tetrahedral intermediate [33a].…”
Section: Resultsmentioning
confidence: 99%
“…Deviations from Hammett plots based on standard σ galues have been rarely reported in S N Ar reactions, but have been commonly observed in the S N 2 process 33,34. Koh and coworkers, for example, investigated the reactions of substituted phenacyl bromides with pyridines in acetonitrile at 45°C and the curved Hammett plots have been interpreted in terms of a change in the rate‐determining step from breakdown to formation of a tetrahedral intermediate [33a].…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey reveals that deviations from Hammett plots based on standard σ‐values have absolutely no report of any systematic study on σ‐complexation reactions, but have been commonly observed in S N Ar or S N 2 process . Um and Bae investigated the reactions of 4‐pyridyl X‐substituted‐benzoates (X = 3,5‐(NO 2 ) 2 , 4‐NO 2 , 3‐NO 2 , 4‐CN, 4‐Cl, H, 4‐Me, 4‐OMe, and 4‐NMe 2 ) with piperidine in acetonitrile at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…TS III ) is responsible for the unusually small β nuc value found for the uncatalyzed reaction of 7 to a certain degree. Another plausible reason for the small β nuc value can be found from the report that β nuc is smaller for reactions of substrates possessing a CS electrophilic center than for those of substrates bearing a CO electrophilic site …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme , aminolysis of esters has been reported to proceed either through a concerted mechanism with a second‐order rate constant ( k c ) or via a stepwise pathway with one or two intermediates, i.e . a zwitterionic tetrahedral intermediate T ± and its deprotonated form T − . Factors suggested to affect the reaction mechanism include type of the reaction medium (protic or aprotic), nature of the electrophilic center (CO, CS, PO, PS and SO 2 ), basicity of the leaving group and incoming amine, etc …”
Section: Introductionmentioning
confidence: 99%